2006
DOI: 10.1021/jp064777b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ultrathin WO3 Nanodisks Utilizing Long-Chain Poly(ethylene glycol)

Abstract: Metal oxide nanostructures hold great potential for photovoltaic (PV), photoelectrochemical (PEC), and photocatalytic applications. Whereas thin films of various materials of both nanoparticle and nanorod morphologies have been widely investigated, there have been few inquiries into nanodisk structures. Here, we report the synthesis of ultrathin WO 3 nanodisks using a wet chemical route with poly(ethylene glycol) (PEG) as a surface modulator. The reported nanodisk structure is based on the interaction of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 43 publications
6
79
0
Order By: Relevance
“…The conductivity further increases and the value of activation energy of WO 2.7 NP is about 0.28(3) eV which corresponds to n-type semiconductor-like behavior. Results of WO 3 NPs conductivities and their interpretations as non-stoichiometric (process A) and hydrate (process B) originates from oxygen vacancies and are compatible with similar works that have been carried out in study of WO 3 thin films as a sensing material for detection of atmosphere pollutants [25][26][27][28][29][30][31].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The conductivity further increases and the value of activation energy of WO 2.7 NP is about 0.28(3) eV which corresponds to n-type semiconductor-like behavior. Results of WO 3 NPs conductivities and their interpretations as non-stoichiometric (process A) and hydrate (process B) originates from oxygen vacancies and are compatible with similar works that have been carried out in study of WO 3 thin films as a sensing material for detection of atmosphere pollutants [25][26][27][28][29][30][31].…”
Section: Resultssupporting
confidence: 87%
“…The conductivity is calculated from the experimentally determined resistance R, which is monitored during the three heating and cooling cycles. The activation energy of conduction, E A , was frequently interpreted using the Arrhenius equation between 300 and 700 K. Our results are compatible with the principle results of conductivity of WO 3−x thin films [19][20][21][22][23][24][25][26]. It is obtained from the following formula:…”
Section: Resultssupporting
confidence: 86%
“…The dimensionality of metal oxides has also been widely investigated for 0D, 1D and 2D nanostructures. [23][24][25][26][27] Colloidal wet chemistry, chemical vapor deposition (CVD) and magnetron sputtering have proven versatile in the creation of metal oxides with nanometersized features. [23,[28][29][30][31] It has been found that the charge transport properties of metal oxide nanoparticles-and nanorod-based PEC cells are superior to those of traditional metal oxide thin film cells.…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy conversion into electricity or chemical energy such as hydrogen represents one of the most promising applications of optical properties of nanomaterials [190,[192][193][194][195]231]. For example, dyesensitized solar cells have attracted significant attention since the initial report in 1991 of a power conversion efficiency of 12 % [190].…”
Section: Energy Conversion: Photovoltaics and Photoelectrochemistrymentioning
confidence: 99%